Analisis Rasio Aktivitas dan Rentabilitas Ekonomis pada PT. Wismilak Inti Makmur Tbk - Siri’, Renindi; Todingbua, Manuel; Paridy, Andryanus (YASIN, 2025)
This study aims to determine the level of efficiency per quarter or quarter at PT Wismilak Inti Makmur Tbk in 2020 to 2023. This study uses a quantitative approach with a quantitative descriptive method to evaluate the company's performance in managing assets, inventory, receivables, and fixed assets. Secondary data were obtained from the annual financial reports published on the Indonesia Stock Exchange (IDX). The results of the study indicate that the efficiency of PT Wismilak Inti Makmur Tbk's financial management fluctuates from year to year. Most quarters show a level of inefficiency in managing the company's assets and resources. However, there are several quarters where the company managed to achieve good to very good efficiency, especially in fixed asset turnover and economic profitability. This finding indicates that with the right strategy, the company can improve its efficiency sustainably.